Examining the impact of social stressor stimuli in eliciting physiological reactivity in children and adolescents with autism spectrum disorder: a systematic review and meta-analysis protocol - Samantha Burns; Agnes S K Wong; Earl Woodruff (BMJ Open)
Introduction Stress is not experienced the same by everyone. Some individuals, such as individuals with autism spectrum disorder (ASD), are at risk of heightened sensitivity to stress responses. ASD is a neurodevelopmental disorder commonly characterised by deficits in social communication and social interaction. Among different stressor stimuli, social stressors are particularly worth our attention due to the social and communication challenges inherent in ASD. This study aims to systematically evaluate different social stressor stimuli in eliciting physiological reactivity in ASD, focusing on the children and adolescent population.Methods and analysis We designed a study protocol for this study and submitted it to PROSPERO for systematic review registration. Any studies with children and adolescents with ASD between the ages of 0 and 18 in clinical and community settings will be included. All types of social stressor interventions will be included. The outcome of interest will include studies with physiological activity of the participants being measured, for example, measures related to autonomic functioning, electrodermal functioning and cortisol level. The primary literature sources will be across four electronic databases: MEDLINE, Embase, PsycInfo and CINAHL in August 2021. The second source of literature will be across grey literature, including ProQuest Dissertations & Theses Global and across clinical trial registries in August 2021. Hand searching of references will be performed on the reference lists of all included studies. Two volunteers pursuing postgraduate-level studies will independently search and screen potential studies for eligibility. Finally, all references considered by hand searching will be reviewed by two researchers. The methodological quality of the research will be assessed by adopting the quality assessment used by a previous study. The assessment consists of four primary categories: descriptive validity, internal validity, external validity and statistical conclusion validity.Ethics and dissemination No ethical approval is required for this study. Results will be disseminated through conferences and publications in relevant peer-reviewed journals.PROSPERO registration number CRD42021244039.